Enhancing Student Learning Outcomes Using the Engineering Design Process: A Case Study in a Physics Course - Ngo, Thien Van (Journal of Teaching and Learning)

(untitled) (University of Windsor, 2026)
The study investigated the effectiveness of using the engineering design process (EDP) to enhance student learning outcomes in a physics course. A mixed-methods approach was used in this study. A quasi-experimental pretest-posttest control group (CG) design was applied for the quantitative phase, while a semi-structured interview was employed for the qualitative phase. The study sample consisted of two classes randomly assigned from the Department of Mechanical Engineering at a technical college, which served as the experimental group (EG) and the other as the CG. Before the intervention, the pretest was administered to both groups. The EDP was implemented in the EG during the intervention, whereas the CG was taught using conventional teaching methods. After the intervention, the posttest was administered to both groups, and a semi-structured interview was conducted with eight students in the EG. The quantitative data were analyzed using independent-samples Mann–Whitney U-tests. The qualitative data were analyzed using thematic analysis. The results showed a statistically significant difference in mean scores between the EG and the CG, indicating that learning physics through the EDP model improved students' physics learning outcomes in the EG. Furthermore, the qualitative analysis revealed that students in the EG perceived EDP as an effective and contextually appropriate approach for learning physics within an engineering context.